2001
DOI: 10.1038/84041
|View full text |Cite
|
Sign up to set email alerts
|

Increased dopamine release in the human amygdala during performance of cognitive tasks

Abstract: Accumulating data support a critical involvement of dopamine in the modulation of neuronal activity related to cognitive processing. The amygdala is a major target of midbrain dopaminergic neurons and is implicated in learning and memory processes, particularly those involving associations between novel stimuli and reward. We used intracerebral microdialysis to directly sample extracellular dopamine in the human amygdala during the performance of cognitive tasks. The initial transition from rest to either a wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 28 publications
6
41
0
Order By: Relevance
“…Firstly, in vivo microdialysis studies show that DA levels increase in distinct subnuclei of the amygdala during Pavlovian approach conditioning, during discriminated instrumental training, during drug challenge, and during drug-cue exposure in rats (Harmer et al, 1997;Harmer and Phillips, 1999;Hori et al, 1993;Weiss et al, 2000). Amygdalar DA also increases in humans during reading or performance of a working memory task (Fried et al, 2001). Secondly, immunohistochemical data corroborate the finding that DA activity is elevated in the amygdala during Pavlovian conditioning and during instrumental conditioning (Phillips et al, 2003).…”
Section: Da In the Amygdala Mediates The Acquisition Of Significance supporting
confidence: 71%
“…Firstly, in vivo microdialysis studies show that DA levels increase in distinct subnuclei of the amygdala during Pavlovian approach conditioning, during discriminated instrumental training, during drug challenge, and during drug-cue exposure in rats (Harmer et al, 1997;Harmer and Phillips, 1999;Hori et al, 1993;Weiss et al, 2000). Amygdalar DA also increases in humans during reading or performance of a working memory task (Fried et al, 2001). Secondly, immunohistochemical data corroborate the finding that DA activity is elevated in the amygdala during Pavlovian conditioning and during instrumental conditioning (Phillips et al, 2003).…”
Section: Da In the Amygdala Mediates The Acquisition Of Significance supporting
confidence: 71%
“…Consistent with these findings, recent studies using voxel-based morphometry have shown an association of FSIQ with the density of GM and WM in regions of the frontal, parietal, temporal, and occipital lobes that subserve verbal and performance abilities (Haier, Jung, Yeo, Head, & Alkire, 2004;Thompson et al, 2001). In addition, a vast number of animal and human studies have suggested that mesolimbic structures, including the hippocampus and amygdala, also play an important role in learning, memory, and cognition (Bechara, Damasio, & Damasio, 2003;Burns, Everitt, & Robbins, 1999;Everitt et al, 1999;Fried, Cameron, Yashar, Fong, & Morrow, 2002;Fried et al, 2001;Jones-Gotman, 1986;Kahn et al, 2002;Squire, Stark, & Clark, 2004). Moreover, the volume of the hippocampus has been shown to correlate positively and significantly with IQ in healthy adults (Andreasen, Flaum, Swayze, O'Leary, et al, 1993), although another more recent study using voxel-based morphometry failed to demonstrate any correlation of IQ with volumes of GM or WM volume in mesolimbic structures (Haier, et al, 2004).…”
Section: Introductionsupporting
confidence: 58%
“…There is increasing evidence that amygdala is involved in positive reward assessment as well as its more familiar role in fear (Baxter and Murray, 2002;Schultz, 2002). Recently, Fried et al, (2001) have shown through micro dialysis that the dopaminergic input to the amygdala in human subjects increases during cognitive tasks not involving fear.…”
Section: Discussionmentioning
confidence: 99%